PENGATURAN DAN PENERAPAN PRINSIP PARITAS CREDITORIUM DALAM HUKUM KEPAILITAN DI INDONESIA - Rizki Agung Firmansyah, Raden; Sekar, I Dewa Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014)
Principle of paritas creditorium, pari passu prorata parte and structuredprorata shall be considered as fundamental principles in debt settlement between debtorand its respective creditor. Principle of paritas creditorium (equality amongcreditors) shall determine equal rights of creditor over the properties belonged by thedebtor. In circumstances of default by debtor, all properties therein shall be in thepossession of the creditor. This writing shall illustrate the principle of paritascreditorium within Law Number 37 of 2004 concerning Bankruptcy and Delayment of DebtSettlement Obligation and its enforcement in Indonesia judgement of law. Method appliedin this research shall be normative legal research by analyzing statutory laws andrespective literatures. Principle of paritas creditorium guarantees the equality of creditorrights to the debtors in the matter of applying bankrupt claim and debt settlement claim.
Keywords: paritas creditorium, bankruptcy law, Indonesia